A rare cause of inguinal abscess: perforated appendicitis due to foreign body in Amyand's hernia - Tartar, Tugay; Sarac, Mehmet; Bakal, Unal; Onur, Mehmet Ruhi; Kazez, Ahmet (Turkish J Pediatrics, 2020)
Background. Amyand's hernia is rarely noted in children, and appendicitis caused by a foreign body in Amyand's hernia is even rarer. Case. A 2-year-old girl presented with recurrent conglomerate lymph node enlargements and an abscess in the right groin existing for one year despite medical treatment. Direct radiography revealed a foreign body in the right inguinal region. Computed tomography showed a foreign body and soft tissue inflammation in the inguinal canal. Laparotomy was performed, and Amyand's hernia was diagnosed. A foreign body was found in the lumen of the appendix vermiformis causing perforated appendicitis. This case is presented because of its rarity and unusual clinical presentation. Conclusion. Amyand's hernia should be considered in paediatric cases with the history of recurrent inguinal abscesses.
Keywords: Amyand's hernia; inguinal abscess; perforated appendicitis; foreign body